Subjective perception of time as a temporal fictional image - Gaukhar I. Issina, Ella V. Nesterik,; Darina Y. Amanbekova, Fazira A. Kakzhanova (Opción, 2019)
The article is concerned with subjective perception of time, also known as psychological time, in the capacity of a textual category and a fictional image via comparative qualitative research methods. As the basis for this hypothesis in its turn we refer to the results of similar investigations in literary studies, psychology and text linguistics. As a result, words describing real fictional time and space quite often appear in descriptions of psychological time. In conclusion, the category of fictional time plays a very important role in the modeling of the subjective perception of time by characters.